Improving acne keloidalis nuchae with targeted ultraviolet B treatment: a prospective, randomized, split‐scalp comparison study. (1st October 2014) - Okoye, G.A.; Rainer, B.M.; Leung, S.G.; Suh, H.S.; Kim, J.H.; Nelson, A.M.; Garza, L.A.; Chien, A.L.; Kang, S.
Summary: Background: Acne keloidalis nuchae (AKN) is a chronic scarring folliculitis with fibrotic papules on the occipital scalp. Its treatment is limited and unsatisfactory. Objectives: To determine whether targeted ultraviolet B (tUVB) phototherapy will (i) improve the clinical appearance of AKN and (ii) induce extracellular matrix remodelling in affected lesions. Methods: Eleven patients with AKN were enrolled in a prospective, randomized, split‐scalp comparison study. One randomly selected side of the scalp was treated with tUVB up to three times weekly for 8 weeks. After week 8, both sides were treated for eight additional weeks. Assessment included lesion counts in two 3 × 3‐cm regions of interest (ROIs), one on each side of the scalp (ROI‐1: tUVB weeks 0–16, ROI‐2: tUVB weeks 9–16), patient self‐assessment and analysis of MMP1, MMP9, TGFB1 and COL1A1 mRNA expression by quantitative reverse‐transcription polymerase chain reaction. Results: Before treatment, the mean lesion count was similar between tUVB‐treated and untreated sides (14·8 vs. 15·0). After 8 weeks of tUVB, the mean lesion count decreased significantly to 9·4 ± 1·2 ( P  =  0·03), with no change on the untreated side. With continued treatment, the mean lesion count in ROI‐1 decreased further to 7 ± 1·5 ( P  = 0·04) after 16 weeks of tUVB. Conclusions: tUVB significantly improved the clinical appearance of AKN, led to patient satisfaction and was well tolerated. Abstract : What's already known about this topic? Acne keloidalis nuchae (AKN) is a chronic scarring perifolliculitis with limited treatment options. Ultraviolet (UV) radiation has anti‐inflammatory, immunosuppressive and antifibrotic effects. What does this study add? Targeted UVB significantly improves the clinical appearance of AKN and is well tolerated. Targeted UVB increases MMP1, MMP9, TGFB1 and COL1A1 expression in AKN lesions, suggesting active matrix remodelling.